Association between dietary index for gut microbiota and osteoarthritis in the US population: the mediating role of systemic immune-inflammation index - Song, Jiulong; Fu, Jian (Frontiers in Nutrition, 2025)
ObjectiveOsteoarthritis (OA) is one of the most prevalent chronic conditions among the elderly. The dietary index for gut microbiota (DI-GM) is a novel proposed indicator reflecting gut microbiome diversity. However, the role of DI-GM in OA remains unclear. This study thus aims to explore the association between DI-GM and the risk of OA and analyze the mediating roles of systemic immune-inflammation index (SII).MethodsWe utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 2007-2018. OA was assessed through self-reported questionnaires, and dietary recall data were used to calculate the DI-GM. Univariate and weighted multivariate logistic regression analyses were employed to evaluate the association between DI-GM and OA, the weighted linear regression analyses were employed to investigate the association of DI-GM with SII, while restricted cubic splines (RCS) curves were used to assess the non-linear relationship between these variables. Subgroup analyses were subsequently conducted to validate the robustness of the findings. Mediation analysis evaluated the role of SII.ResultsThis study included 15,875 participants, revealing a significant inverse association between the DI-GM and OA risk (p < 0.001), higher DI-GM demonstrated a substantially reduced OA risk (adjusted model OR: 0.83; 95% CI: 0.79–0.86) and were negatively associated with the SII [β (95% CI): –9.2 (–13.0, –2.0)]. The RCS curve indicated a non-linear relationship between DI-GM and OA risk. Subgroup analysis showed that various demographic and clinical factors did not significantly alter the association between DI-GM and OA risk (interaction p-value > 0.05). The mediating effect of SII accounted for 12.69% of association between DI-GM and OA.ConclusionThis study found a significant negatively association between DI-GM and OA prevalence in the US population. Mediation analyses demonstrated a significant mediating effect of SII.